Gamma-aminobutyric acid-functionalized naphthalene diimide for aqueous organic flow batteries - Shahsavan Mahsa; Wiberg Cedrik; Peljo Pekka (Royal Society of Chemistry, 2022)
An anionic gamma-aminobutyric acid-functionalized naphthalene diimide (GABA-NDI) was investigated for its possible application in flow batteries. A GABA-NDI/ferrocyanide flow battery was stable over 200 cycles and demonstrated an average coulombic efficiency of 99.96% and an excellent energy efficiency of 80.9% at 60 mA cm−2 while accessing 95% of the theoretical capacity of GABA-NDI. An increase in solubility and stability was achieved compared to previous studies.